f ( n ) : = a = 1 ∏ p n b = 1 ∏ p n ( 1 + p n p n e 2 π i a b / p n )
Let { p n } n = 1 ∞ = { 3 , 5 , 7 , 1 1 , … } be the sequence of odd prime numbers in increasing order. Let us define the function above. Compute n = 1 ∑ 2 0 1 6 ( 1 + p n p n p n ( 1 + p n ) f ( n ) − p n + n ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
First let us fix a ∈ { 1 , 2 , … , p n − 1 } . We observe that p n p n e 2 π i b / p n for b = 1 , 2 , … , p n are all the roots of the polynomial P ( x ) : = x p n − p n . Moreover, since a is relatively prime to p n (for p n is prime and a < p n ), p n p n e 2 π i a b / p n are also the roots of the same polynomial (not necessarily in the same order). Therefore,
− 1 − p n = P ( − 1 ) = b = 1 ∏ p n ( ( − 1 ) p n − p n p n e 2 π i b / p n ) = b = 1 ∏ p n ( − 1 − p n p n e 2 π i b / p n ) , (notice that p n is odd, so ( − 1 ) p n = − 1 .)
Thus, we deduce that
a = 1 ∏ p n − 1 b = 1 ∏ p n ( 1 + p n p n e 2 π i b / p n ) = a = 1 ∏ p n − 1 ( 1 + p n ) = ( 1 + p n ) p n − 1 .
Now, when a = p n ,
b = 1 ∏ p n ( 1 + p n p n e 2 i p n b / p n ) = b = 1 ∏ p n ( 1 + p n p n ) = ( 1 + p n p n ) p n .
Hence, f ( n ) = a = 1 ∏ p n b = 1 ∏ p n ( 1 + p n p n e 2 π i a b / p n ) = ( 1 + p n ) p n − 1 ( 1 + p n p n ) p n .
Now it is simple to compute
n = 1 ∑ 2 0 1 6 ( 1 + p n p n p n ( 1 + p n ) f ( n ) − p n + n ) = n = 1 ∑ 2 0 1 6 ( 1 + p n p n p n ( 1 + p n ) ( 1 + p n ) p n − 1 ( 1 + p n p n ) p n − p n + n ) = n = 1 ∑ 2 0 1 6 ( 1 + p n p n ( 1 + p n ) ( 1 + p n p n ) − p n + n ) = n = 1 ∑ 2 0 1 6 ( 1 + p n − p n + n ) = n = 1 ∑ 2 0 1 6 ( 1 + n ) = 2 0 1 6 + 2 2 0 1 6 ⋅ 2 0 1 7 = 2 0 3 5 1 5 2 .